Traumatology and orthopedics’ discipline directions and formation in the course of Bologna process - Yu. V. Sukhin, Yu. V.; Pavlychko, Yu. Ty.; Topor, V. P. (Journal of Education, Health and Sport, 2017)
Modern teaching program which exists now in traumatology and orthopedics studying is undeveloped and requires many changes before it’s put into action.Ukraineprematurely entersBolognaprocess, teaching has all elements of European education.Ukraine’s accession to theBolognasystem of education testifies more its desire to enter theEuropeanCommonwealthbut not the necessity to improve the quality of education.